Characterization of silicon surfaces implanted with silver ions at low energy using spectroscopic ellipsometry. (February 2018) - Bazarov, V.V.; Nuzhdin, V.I.; Valeev, V.F.; Stepanov, A.L.
Abstract: An amorphous silicon ( α-Si ) layers formed on the surface of single-crystal substrate ( c-Si ) by low-dose implantation with silver ions were studied by spectroscopic ellipsometry. Ion implantation of c-Si was carried out with energy of 30 keV, current density varied from 0.1 to 5 μA/cm 2 and with doses in the range of 6.24·10 12 –1.3·10 16 ion/cm 2 . The effect of non-linear increase in the generation rate of radiation defects with a grow of current density was observed and discussed. Highlights: Formation of the Si amorphous layer at the Ag + ion implantation has been studied. The amorphous phase content in the implanted layer was analyzed for a heated target. An increase of disorder value in the case of the dose rate increase was investigated.